Implementasi Pendidikan Nilai Moral dan Karakter dalam Pembelajaran PPKn di SMP Negeri 17 Medan 2022-2023 - Eko Pranata Sinaga; Hera Septiana Siahaan; Rose Venerius Sirait; Sri Yunita (Journal on Education, 2023)
In learning Pancasila and Citizenship Education (PPKn), morals and character are the main things that need to be instilled in every child, because the Civics learning process currently has a goal in forming children's morals and character. The implementation of moral and character values in Civics learning at SMPN 17 Medan in 2022-2023 is one of the focuses for educators at this school. This is done as an effort to improve the quality of education and form young people who have good personalities and morals. Educators at SMPN 17 Medan have made various efforts for the success of this implementation, such as integrating values and character into learning, holding extracurricular activities that support character building, and implementing an appropriate system of rewards and sanctions for each student's behavior that influences character. Factors that affect the morale and character of children are environmental factors, friends, and media or technology factors. In this study the method used is a qualitative approach which is carried out descriptively. The basis or theory of the discussion this time is obtained from the results of literature or literature studies obtained from several relevant sources such as journals, articles and books.